ACTIVATED ZINC PYRITHIONE APPLICATION FOR THE ATOPIC DERMATITIS AMONG CHILDREN: MECHANISM OF ACTION, CLINICAL EFFICIENCY - F.I. Petrovsky; D.S. Korostovtsev (Педиатрическая фармакология, 2009)
Atopic dermatitis is characterized by the chronic recurrent course and often complicated by the consecutive infection and requires an adequate and regular external treatment. This article is devoted to the overview of the key pharmacodynamic and clinical effects of the activated zinc pyrithione for the atopic dermatitis. The activated zinc pyrithione has an expressed, antiinflammatory, proapoptogenic, antifungal and antibacterial effect, owing to which it affects all the components of the atopic dermatitis pathogenesis. The research with nessed the high efficiency and safety of this medication for atopic dermatitis in children, which allows the researchers to classify it as the efficient non steroid medications for the external treatment for the atopic dermatitis among children.Key words: atopic dermatitis, treatment, activated zinc pyrithione, children.